(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
The first two contributions included below, respectively by Alberto Cadioli and Giuseppe Frasso, offer a summary of what was discussed on April 4, 2017, at the Biblioteca Ambrosiana, during the meeting Why Publish Today New Philology Journals?, that followed the presentation of the first issue of our journal (see the poster attached here as PDF full text). To these two first contributions are added others that widen the debate, and will be gradually loaded in this section of PEML. Furthermore, the issues addressed by the various stakeholders can be related to wider reflections. About them, see the following links: http://btfp.sp.unipi.it/it/2017/06/ri-viste/ https://theconversation.com/quest-ce-quune-revue-scientifique-et-quest-ce-quelle-devrait-etre-77986